Penerapan Manajemen Pembelajaran Daring di Sekolah Menengah Pertama Negeri Karang Jaya Musi Rawas Utara - Yanto, Murni; Zulaiha, Siti (QUALITY, 2022)
The purpose of this study is to find out how the implementation  of  online  learning at karang jaya Musi Rawas utara Junior High School which carried  out online learning during covid-19 pandemic. This type  of research  is qualitative. Implementation  of  online learning  at Karang Jaya Musi Rawas Utara  Junior high school :(a) educators  use a strategy  of  utilizing teaching time, then  teachers also provide reinforcement and enrichment  using  online media (b) the teaching  method used  is collaboration  between  face-to-face learning and  teaching  methods online learning (c) the learning  media used  are  electronic media and the used of online based aplications such as WhatApp,Google Meet and  Zoom. (d)evaluation of online learning which carried out.